Comprehensive Surveillance of Virus Infection among Captive African Pygmy Hedgehogs in Japan - Koizumi, Iori; Tsukada, Hina; Hayasaka, Daisuke; Shimoda, Hiroshi (Viruses, 2022)
African pygmy hedgehogs (Atelerix albiventris) are popular exotic pets in Japan, and their breeding numbers have recently increased. Although various diseases have been reported in hedgehogs, including skin, respiratory, neurological, and neoplastic diseases, most of the causes remain unidentified. In this study, we investigated herpesvirus, adenovirus, and coronavirus infections among 150 African pygmy hedgehogs in Japan and evaluated the correlations between virus infection and diseases. A novel herpesvirus named Atelerix albiventris herpesvirus 1 (AAHeV), and African pygmy hedgehog adenovirus 1 (AhAdV-1) were detected in 14 and 3 oral swab samples, respectively. AAHeV infection may be related to neurological clinical signs. Interestingly, no hedgehog with a neoplastic disorder tested positive for AAHeV. Further research is required to determine the pathogenicity and prevalence of the detected viruses.